Rhinovirus viremia in children with respiratory infections - Xatzipsalti, M.; Kyrana, S.; Tsolia, M.; Psarras, S.; Bossios, A.; Laza-Stanca, V.; Johnston, S. L.; Papadopoulos, N. G. (Am J Respir Crit Care Med, 2005)
{Viremia has been implicated in many viral infections; however, viremia due to rhinovirus (RV; rhinoviremia) has been considered not to occur in normal individuals.|To evaluate whether RV enters the bloodstream and identify the possible risk factors.|Nasopharyngeal washes (NPWs) of 221 children with respiratory infections were examined for the presence of RV by reverse transcription-polymerase chain reaction. Blood from 88 children, whose NPW was RV-positive, and 31 of RV-negative control subjects was subsequently examined for the presence of RV in the blood by semi-nested reverse transcription-polymerase chain reaction. Rhinoviremia was then correlated with clinical characteristics of the disease.|RV was detected in the blood of 10 out of 88 NPW RV-positive cases (11.4%): 7 of 28 children with asthma exacerbations (25.0%), 2 of 26 with common cold (7.7%), 1 of 25 with bronchiolitis (4.0%), and 0 of 9 with pneumonia (0%). All NPW RV-negative cases were negative in the blood. The proportion of rhinoviremia in children with asthma exacerbation was significantly higher compared with children suffering from the other diseases (25 vs. 5%
Keywords: Acute Disease Adolescent Asthma Bronchiolitis Case-Control Studies Child Child; Agar Gel Female Greece Hospitals; Pediatric Humans Infant Logistic Models Male Multivariate Analysis Nasal Lavage Fluid Pneumonia; Preschool Common Cold DNA; Viral Electrophoresis; Viral Reverse Transcriptase Polymerase Chain Reaction Rhinovirus Risk Factors Severity of Illness Index Viremia